Key factors for the direct growth of zeolite faujasite (FAU) on metallic aluminum surface - Chanda, Rajesh; Selvam, Thangaraj; Avadhut, Yamini; Kuhnt, Andreas; Herrmann, Ralph; Hartmann, Martin; Schwieger, Wilhelm (Microporous and Mesoporous Materials, 2018)
Zeolite faujasite (FAU) is widely used as a catalyst and adsorbent in many industrial catalytic and separation applications. The high water adsorption capacity of zeolite FAU makes it an attractive adsorbent material for the heat pump and heat storage applications. However, highly alkaline condition, which is required for the synthesis of zeolite FAU, is a challenge to achieve FAU/aluminum composites via a direct, reactive coating approach. In this contribution, a reactive coating method to fabricate zeolite FAU based aluminum composites is presented. The impact of important synthesis paramaters on the formation of such composites is discussed based on thorough characterization (such as XRD, SEM, MAS NMR, N-2- and water-sorption) of the coated FAU layer (the composite) and so-called excess powder, formed parallel in the reaction solution. Along with the comprehensive study of zeolite FAU formation as a coating layer, preliminary results of the fabricated composites in potential heat pump application are presented as well.
Keywords: Zeolite; Crystal growth; Coating; Heat pump; Thin film